Influence of destination image, augmented reality and destination social responsibility on destination beliefs, motivation and intention to visit of tourists which are moderate by digital Wom in Berau District, East Kalimantan - Nurhidayati, Safitri; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (Edelweiss Applied Science and Technology, 2024)
This research aims to prove and analyze the influence of destination image, augmented reality and destination social responsibility on destination trust, motivation and intention to visit moderated by digital word of mouth (WOM) in Berau Regency, East Kalimantan. The sample in this study was 247 respondents. The sampling technique uses purposive non-probability sampling. The data analysis technique in this research is validity and reliability testing using the SPSS V23 application and hypothesis testing using SEM-AMOS. The results of this research show that destination image has a significant effect on destination trust, destination image has a significant effect on motivation, destination image has a significant effect on intention to visit, augmented reality has a significant effect on destination trust, augmented reality has a significant effect on motivation, destination social responsibility has a significant effect on destination trust, destination trust has a significant effect on intention to visit, motivation has a significant effect on intention to visit, augmented reality has a significant effect on intention to visit tourist destinations in Berau Regency, East Kalimantan, unacceptable, destination social responsibility has a significant effect on intention to visit in tourist destinations in Berau Regency, East Kalimantan, is also unacceptable. The role of digital WOM as a moderator of destination trust on intention to visit is significant.